Strategic Planning for Employment Self-Containment in Metropolitan Sub-Regions. Issue 1 (2nd January 2018) - Martinus, Kirsten; Biermann, Sharon
Abstract: Metropolitan strategic plans often focus on strengthening local employment opportunities to address the congestion and commuting issues threatening city sustainability. The success of such strategies relies on a more equitable distribution of jobs between sub-regions and can be comparatively benchmarked through one of the three related measures of employment self-sufficiency, self-containment or jobs-housing balance. However, in practice, planning policy implementation to meet these targets seldom reduces automobile commuting. This paper investigates self-containment across a range of occupation and industry types to highlight large differences in commuting and employment patterns through a case study of Perth's Northwest sub-region, Western Australia. Its findings suggest the application of current sub-regional policy and targets within Perth may reinforce the wage and skill disadvantage of outer metropolitan sub-regions over the inner core. It recommends a more nuanced understanding of these measures taking into account the complex dynamics of both employment opportunities and commuting patterns across sub-regions of a city.